Theory of rare gas alloys: heat capacity: Classical Cryocrystals - Bagatskii, M.I.; Feodosyev, S.B.; Gospodarev, I.A.; Kotlyar, O.V.; Manzhelii, E.V.; Nedzvetskiy, A.V.; Syrkin, E.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Low-temperature heat capacity of cryocrystals, which contain impurity clusters has been investigated theoretically and experimentally. Such defects might essentially enrich low-frequency part of the phonon spectrum by introducing both localized and delocalized vibrations. The effect of both types of the vibrations on the temperature dependence of the heat capacity is analyzed. Heat capacity of the disordered solid solution Kr–Ar (Ar concentration is 25%) is studied as an example of the effect of the light weakly connected impurities on the low-temperature thermodynamic characteristics of the system. The mass defect of such an impurity induces «phonon pumping» from the low-frequency part of the spectrum into the high-frequency part and decreasing the low-temperature heat capacity, while the weakened interaction between the impurity and the host atoms combined with even weaker interaction between the impurities leads to the formation of the low-temperature maximum on the heat capacity temperature dependence. The analysis performed shows that at rather high Ar concentrations, the nonmonotonous temperature dependence of the relative change in the heat capacity of solid Kr1-pArp solutions is determined by excitation of delocalized high-dispersion low-frequency phonons.